P3.067 Prevalence of Chlamydia Trachomatis and Neisseria Gonorrhoeae in High School Students Between 14 and 19 Years-Old Using a Non-Invasive Technique. (13th July 2013) - Paredes, M; Gomez, Y; Torres, M; Fernandez, M; Tovar, M
Abstract : Introduction: Chlamydia trachomatis (Ct) and Neisseria gonorrhoea (Ng) are two of the most prevalent sexually transmitted infections (STI) in the world and affect mostly women younger of 25 years old causing sequels in their sexual health and fertility. Objective: to determine the prevalence of Ct and Ng of high school students in the centre area of the Cundinamarca, Colombia and associated factors for their infection. Methods: a cross-sectional study was developed. 1875 students between 14 and 19 years old of high school were identified in 11 small cities of a Colombian state. The selected students filled out a survey and gave a sample of urine for the detection of Ct and NG using real-time PCR. Before the survey, sexual health lectures were given to students, teachers and parents. Results: a sample of 972 sexually active students was obtained. The prevalence of Ct was 2.24% (1.28–3.19 95% CI) and Ng 0.09%.(0%–0.28% 95% CI) No coinfection was detected. 21.4% of the girls with CT were asymptomatic (3/14). A association was identified between Ct and gender (chi2: 5.2, p:0.024), consume of psychoactive substances during the last sexual intercourse (chi2 4.4, p: 0.048) y previous diagnosis of STI of their partner (chi2: 9.0; p: 0.006). 34.1% of the men and 79% of the women with Ct or Ng reported at least one symptom of STI in the last 3 months. Conclusions: This is the first study in Colombia using non-invasive techniques for the detection of Chlamydia and gonorrhoea. The prevalence of Ct and the frequency of asymptomatic cases were below compared with other studies. This can be explained because the area of the study is rural and some studies have shown differences between rural and urban areas. The population has a high frequency of symptoms which can be associated to other STIs and genital infections